Foreign-catalyst-free growth of InAs/InSb axial heterostructure nanowires on Si (111) by molecular-beam epitaxy. (3rd March 2017) - So, Hyok; Pan, Dong; Li, Lixia; Zhao, Jianhua
Abstract: Epitaxial high-quality InAs/InSb axial heterostructure nanowires are of great interest due to their distinct advantages in fundamental research as well as applications in semiconductor electronic and quantum devices. Currently, nearly all the growth of InAs/InSb axial heterostructure nanowires is assisted with foreign catalysts such as Au, and work on foreign-catalyst-free growth of InAs/InSb axial heterostructure nanowires is lacking. Here we report on the growth of InAs/InSb axial heterostructure nanowires on Si (111) substrates by molecular-beam epitaxy without using any foreign catalysts. The Sb/In beam equivalent pressure (BEP) ratio is found to have important influence on the heterostructure nanowire morphology, and InSb nanowires can be epitaxially grown on InAs nanowire stems with a hexagonal prism and nanosheet-like shapes when the Sb/In BEP ratio varies from 10 to 20. Transmission electron microscopy studies reveal that the InAs nanowire stems have a mixture of zincblende (ZB) and wurtzite (WZ) crystal structures, while InSb nanowire parts have a pure ZB crystal structure free of stacking faults. Composition analysis of axial heterostructure nanowires provides clear evidence that the InSb nanowires are epitaxially grown on InAs nanowires in an In self-assisted vapor–liquid–solid manner. This study paves a new route for growing narrow-gap semiconductor heterostructures with strong spin–orbit interaction for the study of topological states, and the growth manner presented here is expected to be used to grow other In-based axial heterostructure nanowires.